2014
DOI: 10.1155/2014/529790
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Duration: A Survival Analysis—Data from a Regional Immunization Survey

Abstract: Objective. To report the duration of and factors associated with exclusive and any breastfeeding among the French-speaking community of Belgium (Wallonia). Material and Methods. A two-stage cluster sample was drawn from the population of children aged 18–24 months living in the area in 2012. Anamnestic data on breastfeeding and sociodemographic information were collected from 525 mothers. Cox's proportional hazards model was used to identify factors associated with discontinuing breastfeeding. Results and Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
1
23
1
5
Order By: Relevance
“…Also, in the ELFE study, women who postponed their return to work by at least 15 weeks after the end of legal maternity leave were more likely to breastfeed for a long duration. Similarly, returning to work earlier has been associated with shorter breastfeeding duration in previous studies (Bonet et al, 2013;Hawkins et al, 2007a;Mandal et al, 2010;Robert, Coppieters, Swennen, & Dramaix, 2014;Skafida, 2012). Some studies specifically investigated the effect of paid maternity leave on breastfeeding duration.…”
Section: Maternal Return To Workmentioning
confidence: 78%
“…Also, in the ELFE study, women who postponed their return to work by at least 15 weeks after the end of legal maternity leave were more likely to breastfeed for a long duration. Similarly, returning to work earlier has been associated with shorter breastfeeding duration in previous studies (Bonet et al, 2013;Hawkins et al, 2007a;Mandal et al, 2010;Robert, Coppieters, Swennen, & Dramaix, 2014;Skafida, 2012). Some studies specifically investigated the effect of paid maternity leave on breastfeeding duration.…”
Section: Maternal Return To Workmentioning
confidence: 78%
“…In the Wallonian context, little adequate BF support exists (except for lactation consultants or limited advice available by phone). In an earlier study, we observed that perceived milk insufficiency, breast engorgement, and cracked nipples accounted for more than 45% of reasons for weaning during the first 3 months (Robert, Coppieters, Swennen, & Dramaix, , ). These issues do require trained personnel, which is scarce in Belgium, (Benahmed, ), as in other countries (Morris, ; Pound, Williams, Grenon, Aglipay, & Plint, ; Sims, Long, Tender, & Young, ).…”
Section: Discussionmentioning
confidence: 97%
“…The determinants of BF vary in magnitude and effect between different populations. 5,6 Feira de Santana, in the countryside of the state of Bahia, has been highlighted due to its BF indicators and its work supporting BF. Noteworthy institutions include the city's implementation of the first human milk bank (HMB) in the state and the Breastfeeding Incentive Center (Centro de Incentivo em Aleitamento Materno---CIAMA), references in the state of Bahia, in addition to two IHAC-accredited hospitals, measures that allowed the implementation of actions to promote breastfeeding.…”
Section: Introductionmentioning
confidence: 99%